Miocene adakitic volcanism in eastern Lhasa Terrane, Tibet: perspective from zircon U–Pb geochronology, whole-rock geochemistry and Sr–Nd–Hf isotopes. Issue 14 (6th August 2022) - Zhou, Bin; Han, Kui; Xie, Chaoming; Zhu, Weipeng; Pan, Liang; Qiao, Xinxing; Zeng, Zhongcheng; Lai, Chunkit; Fan, Peng
ABSTRACT: The Riduo intermediate-felsic volcanic rocks are located in the eastern Lhasa terrane in southern Tibet. Zircon U–Pb dating, geochemical and Sr–Nd–Hf isotope analyses were carried out to constrain the age, petrogenesis and magma source of the Riduo magma suite, including andesite, dacitic tuff, and quartz diorite. Zircon U–Pb dating yielded Early Miocene ages of 19.5 ± 0.5 Ma (andesite), 17.6 ± 0.3 Ma (dacitic tuff), and 15.6 ± 0.5 Ma (quartz diorite). Geochemically, this early Miocene suite is adakitic with high SiO2 (55.76–69.46 wt.%), Al2 O3 (15.21–16.61 wt.%), Na2 O (3.82–4.83 wt.%), Sr (427–1033 ppm), and Sr/Y (24.5–145), but low Y (< 17.8 ppm) and Yb (< 1.82 ppm). The rocks also have low to high K2 O (0.44–3.82 wt.%). They are enriched in light rare earth elements (LREEs), large ion lithophile elements (LILEs, e.g. K, Rb, Th and U), but depleted in high-field strength elements (e.g. Nb, Ta) and heavy rare earth elements (HREEs), and have weakly negative to positive Eu anomalies. Isotope analyses reveal that most samples have high whole-rock initial 87 Sr/ 86 Sr ratios (0.705611–0.708807), low εNd (t) (−2.25 to −1.15), and positive zircon εHf (t) (+1.29 to +6.49). We suggest that the early Miocene magmas in the eastern Lhasa terrane were likely sourced from post-collisional partial melting of the juvenile lower crust with minor mantle input. The magmas may have been crustal-contaminated during their ascent to the upper crust along the N-S-trending Cona-Riduo rift.